2020
DOI: 10.1037/pst0000297
|View full text |Cite
|
Sign up to set email alerts
|

“We can work it out”: Working through termination ruptures.

Abstract: Supportive-expressive (SE) psychodynamic treatment is based on the identification of and working through the patient’s signature core conflictual relationship theme. According to the SE framework, when termination is anticipated, separation conflict arises, and the actualization of the patient’s interpersonal wish in the relationship with the therapist is no longer possible. The disactualization of the patient’s wish in the relationship with the therapist may cause patients to regress to their maladaptive prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Marx and Gelso (1987) found that a client's loss history predicted the importance they placed on discussing their reactions during termination. Ben David-Sela et al (2020) examined how clients end treatment and found that the majority of clients felt regulated with a sense of gratitude except for clients who suffered from Cluster B personality disorders (PD). These personality disorders include borderline PD, narcissistic PD, and antisocial PD.…”
Section: Endings and The Client's Past: History Of Loss Trauma And Pe...mentioning
confidence: 99%
See 1 more Smart Citation
“…Marx and Gelso (1987) found that a client's loss history predicted the importance they placed on discussing their reactions during termination. Ben David-Sela et al (2020) examined how clients end treatment and found that the majority of clients felt regulated with a sense of gratitude except for clients who suffered from Cluster B personality disorders (PD). These personality disorders include borderline PD, narcissistic PD, and antisocial PD.…”
Section: Endings and The Client's Past: History Of Loss Trauma And Pe...mentioning
confidence: 99%
“…For example, microaggressions, which are subtle offensive comments that devalue clients based on their different identities, can occur during therapy, and these ruptures can lead to deteriorations in the alliance (Sue, 2010;Sue et al, 2007) and end in unilateral terminations (Vasquez, 2007). Client attachment style (Marmarosh, 2017;Marmarosh & Salamon, 2020;Zilberstein, 2008), personality (Ben David-Sela et al, 2020), and history of loss (Marx & Gelso, 1987) also influence the alliance and termination. Client self-esteem, self-blame, and sense of failure in treatment can impact the experience of ending as well (Baum, 2005).…”
Section: Client Factors That Influence Clients' Experience Of Endings...mentioning
confidence: 99%